Psychological determinants of student achievement in a short-term TOEFL workshop - Jailani, Ahmad; Kamaliasari, Sri; Susilawati; Kurniati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study examines the relationships between three psychological constructs—interest, anxiety, and grit—and academic achievement within a short-term TOEFL preparation workshop. Using a quantitative correlational design, data were collected from 18 prospective English teachers at a state Islamic college in Riau, Indonesia. Participants completed Likert-scale questionnaires measuring interest, anxiety, and grit, alongside pre- and post-intervention TOEFL tests. Spearman’s rank correlation analysis revealed no statistically significant associations between any of the psychological factors and achievement gains. Interest demonstrated a weak negative correlation (ρ = -0.370, p = 0.131), while anxiety (ρ = 0.022, p = 0.931) and grit (ρ = 0.032, p = 0.899) exhibited negligible positive correlations. Linearity tests further confirmed the absence of significant relationships. These findings challenge prevalent assumptions regarding the direct predictive power of psychological traits on short-term test performance in intensive preparation contexts. Instead, they suggest that variables such as instructional quality, baseline language proficiency, and contextual support systems may exert a greater influence on outcomes in brief, focused interventions. Although interest, anxiety, and grit are well-established correlates of long-term academic success, this study indicates their limited role in explaining achievement variance within condensed training formats. The study concludes by recommending further investigation into a broader range of cognitive, instructional, and situational factors that may impact TOEFL performance, particularly in English as a Foreign Language (EFL) settings characterized by limited resources or geographic isolation.